Regulation of Biosynthesis of Individual Cellulases in Thermomonospora fusca - Spiridonov, Nikolay A. (American Society for Microbiology, 1998)
Regulation of the biosynthesis of the six cellulases comprising the cellulolytic system of the thermophilic soil bacterium Thermomonospora fusca ER1 was studied. The levels of the individual enzymes produced on different noninducing and inducing carbon sources were determined. The lowest level of cellulase synthesis (3 nM) was observed with xylose as a carbon source, and the highest level (247 to 1,670 nM for different enzymes) was found in cultures grown on microcrystalline cellulose. Endocellulases and exocellulases showed distinctly different regulation patterns. Differences in the regulation of individual enzymes appear to be determined by the specific structural organization of the upstream regulatory sequences of their genes.